The dual-function of bioactive peptides derived from oyster (Crassostrea gigas) proteins hydrolysates - Dongyang Zhu; Zhen Yuan; Di Wu; Chao Wu; Hesham R. El-Seedi; Ming Du (Food Science and Human Wellness)
Oysters (Crassostrea gigas) have a wide range of functionality due to their nutritional and bioactive components. However, the bioactive peptides of oyster proteins are rarely reported, particularly their anti-diabetes effects and antioxidants. Oyster proteins were extracted from fresh oysters using phosphate-buffered saline and simulated gastrointestinal digestion was performed. The degree of hydrolysis (DH), structural characterization, molecular weight (Mw) distribution, free amino acid, anti-diabetic activity, and antioxidant activity were studied during in vitro simulated gastrointestinal digestion. The results showed that the α-glucosidase inhibitory activity, α-amylase inhibitory activity, DPPH radical scavenging activity, and ABTS radical scavenging activity of the oyster protein gastrointestinal digest were increased (P < 0.05) from 0 to 33.96 %, from 9.17 % to 44.22 %, from 9.01 µg trolox/mg protein to 18.48 µg trolox/mg protein, and from 21.44 µg trolox/mg protein to 56.21 µg trolox/mg protein, respectively. Additionally, the DH, β-turn structure, fluorescence intensity, free amino acid, and short peptide content (Mw < 1000 Da) increased in the simulated gastrointestinal digestion. These results indicate that the digestive hydrolysates obtained from oyster proteins could be used as natural anti-diabetic and antioxidant agents.